Anode layer and anode-supported solid oxide battery containing same

By using organic solvents I and solvent II with a relative dielectric constant difference of greater than 2, the problem of difficulty in balancing the porosity and support strength of the anode layer is solved, and an anode layer with high porosity and high support strength is achieved, and the performance of solid oxide fuel cells is improved.

CN119581594APending Publication Date: 2025-03-07CHAOZHOU THREE CIRCLE GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411628109.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a good balance between the porosity and support strength of the anode layer. Traditional organic pore-making agents are prone to cause internal stress and uneven pore morphology during the sintering process, affecting the electrical performance and service life of the battery.

Method used

Based on the organic solvent I and solvent II whose relative dielectric constant difference value is greater than 2, an anode layer with uniform porosity and pore size distribution is achieved by forming a "core-shell" particle structure, the pore position is evenly distributed, and the pore size size and distribution are controlled to achieve an anode layer with uniform pore size distribution.

Benefits of technology

The porosity of the anode layer is 48-58% and the support strength is 210-380MPa, which improves the power generation efficiency and service life of the solid oxide fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005135238780000071
    Figure BDA0005135238780000071
  • Figure BDA0005135238780000081
    Figure BDA0005135238780000081
  • Figure BDA0005135238780000082
    Figure BDA0005135238780000082
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly discloses an anode layer and an anode-supported solid oxide battery containing the anode layer, the anode layer comprises the following preparation raw materials by mass: 30-50% of mixed powder, 25-50% of an organic solvent, 5-10% of a binder, 1-3% of a dispersant, and 1-20% of a plasticizer; the organic solvent comprises a solvent I and a solvent II, and the difference between the relative dielectric constants of the solvent I and the solvent II is greater than 2; the mass ratio of the solvent I to the solvent II is (0.7-2.7): 1; the mass ratio of the solvent II to the mixed powder is (0.2-0.5): 1. The anode layer adopts the organic solvent as the pore-forming agent, and compared with the existing solid pore-forming agent, the pore size distribution and porosity of the anode layer can be better controlled, so that the prepared anode layer has relatively uniform pore size distribution, relatively high porosity and relatively high supporting strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to an anode layer and an anode-supported solid oxide battery containing the anode layer. Background Art

[0002] Solid oxide cells include solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs). They directly convert chemical energy stored in fuels and oxidants or water into electrical energy under medium and high temperature conditions. They are highly efficient and environmentally friendly all-solid chemical power generation devices. Anode-supported flat-plate cells use the anode layer in the battery structure as the support for the overall structure of the single cell. By thinning the electrolyte layer, the internal resistance of the battery is reduced, thereby increasing the battery output power. They are one of the types of solid oxide cells that are currently being widely studied.

[0003] In order to ensure that the solid oxide battery has high power output and good mechanical strength, the anode layer as a support should have appropriate porosity and support strength at the same time. Generally speaking, the porosity in the anode layer directly affects the length range of the three-phase interface of the battery reaction, determines the gas diffusion rate and the interface reaction efficiency, and thus determines whether the battery has good electrical performance and service life. The pores obtained by sintering the anode layer material itself are too few to achieve the required porosity. In the actual preparation process, a specific pore former will be selected for pore forming treatment. However, the use of pore formers will generate a lot of heat during the high-temperature combustion process, which is easy to form internal stress inside the anode layer and cause battery cracking. On the other hand, the shape of the pore former particles directly determines the morphology of the anode pores. Inconsistent uniformity of the pore former particles used will cause the anode to produce irregularly sized and unevenly distributed pores. A large amount of pore formers is required to form a connected gas transmission channel, and excessive use of pore formers will reduce the support strength of the anode layer and affect the overall electrical performance and service life of the battery. Therefore, the technology of using traditional organic pore formers to expand the porosity in the anode layer is difficult to achieve a good balance between porosity and support strength, and the mixed pore formers composed of multiple components are difficult to completely remove during the sintering process, thereby affecting the electrical performance of the battery itself. Summary of the invention

[0004] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide an anode layer.

[0005] A second object of the present invention is to provide an anode-supported solid oxide battery.

[0006] A third object of the present invention is to provide a method for preparing an anode-supported solid oxide battery.

[0007] A fourth object of the present invention is to provide application of the above-mentioned anode layer in the field of batteries.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides an anode layer, comprising the following raw materials in mass percentage: 30-50% of mixed powder, 25-50% of organic solvent, 5-10% of binder, 1-3% of dispersant, and 1-20% of plasticizer;

[0010] The mixed powder includes ceramic powder and metal oxide;

[0011] The organic solvent includes solvent I and solvent II, the difference between the relative dielectric constants of solvent I and solvent II is greater than 2; the mass ratio of solvent I to solvent II is (0.7-2.7):1; the mass ratio of solvent II to the mixed powder is (0.2-0.5):1.

[0012] When preparing the anode layer of the present invention, the solvent I and the solvent II are based on the difference in relative dielectric constants. The solvent I and the solvent II are not miscible. The solvent I with a large relative dielectric constant has a large wettability to the mixed powder with hydroxyl groups attached to the surface (the surface contact angle between the solvent I and the mixed powder is small). During the mixing process, the solvent I completely wraps the mixed powder to form a "core-shell" granular state. The solvent II with a small relative dielectric constant is evenly dispersed between the "core-shell" granules, plays a role of mutual barrier and exists relatively independently in the anode layer slurry, providing evenly distributed hole positions for the formation of anode layer holes. During the preparation of the anode layer, the solvent I and the solvent II both volatilize, and the solvent II exists between the "core-shell" granules, leaving holes of a specific size after volatilization, and an anode layer with a specific porosity and uniform pore size distribution is obtained after sintering.

[0013] In the raw materials for preparing the anode layer of the present invention, the mass percentage of the mixed powder is 30-50%, for example, it can be selected from 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%.

[0014] In the raw materials for preparing the anode layer of the present invention, the mass percentage of the organic solvent is 25-50%, for example, can be selected from 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%.

[0015] In the raw materials for preparing the anode layer of the present invention, the mass percentage of the binder is 5-10%, for example, can be selected from 5%, 6%, 7%, 8%, 9%, 10%.

[0016] In the raw materials for preparing the anode layer of the present invention, the mass percentage of the dispersant is 1-3%, for example, can be selected from 1%, 1.5%, 2%, 2.5%, 3%.

[0017] In the raw materials for preparing the anode layer of the present invention, the mass percentage of the plasticizer is 1-20%, for example, it can be selected from 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.

[0018] In some embodiments of the present invention, the mass ratio of the solvent I to the solvent II is (0.7-2.7):1, for example, it can be selected from 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, and 2.7:1.

[0019] In some embodiments of the present invention, the mass ratio of the solvent II to the mixed powder is (0.2-0.5):1, for example, can be selected from 0.2:1, 0.3:1, 0.4:1, 0.5:1.

[0020] When the mass ratio of solvent I to solvent II is too small or the mass ratio of solvent II to mixed powder is too large, that is, the relative content of solvent II is too large, the relative content of solvent I is too small, or the relative content of mixed powder is too small, the wettability of solvent I on the mixed powder becomes poor, and the mixed powder cannot achieve a good dispersion effect, resulting in poor uniformity, affecting the pore size and position distribution, and excessive solvent II will cause the porosity to be too large and the support strength to be reduced; when the mass ratio of solvent I to solvent II is too large or the mass ratio of solvent II to mixed powder is too small, that is, the relative content of solvent II is too small, the relative content of solvent I is too large, or the relative content of mixed powder is too large, the pore-forming effect of solvent II is weakened, and the porosity of the obtained anode layer is too small, which affects the improvement of the electrical performance of the battery.

[0021] In some embodiments of the present invention, in the mixed powder, the mass ratio of the ceramic powder to the metal oxide is (1-3):1, for example, it can be selected from: 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1.

[0022] In some embodiments of the present invention, the solvent I is selected from at least one of acetonitrile (relative dielectric constant of 37.5), methanol (relative dielectric constant of 33.6), ethanol (relative dielectric constant of 24.3), acetone (relative dielectric constant of 20.7), isopropanol (relative dielectric constant of 19.92), n-pentanol (relative dielectric constant of 13.9), tert-butanol (relative dielectric constant of 12.47), tetrahydrofuran (relative dielectric constant of 7.58), ethyl acetate (relative dielectric constant of 6.02), chloroform (relative dielectric constant of 4.81), and ether (relative dielectric constant of 4.34).

[0023] In some embodiments of the present invention, the solvent II is selected from at least one of m-xylene (relative dielectric constant of 2.38), toluene (relative dielectric constant of 2.37), benzene (relative dielectric constant of 2.29), carbon tetrachloride (relative dielectric constant of 2.24), dioxane (relative dielectric constant of 2.21), cyclohexane (relative dielectric constant of 2.02), petroleum ether (relative dielectric constant of 1.8), and n-hexane (relative dielectric constant of 1.58).

[0024] In the present invention, the difference between the relative dielectric constants of the solvent I and the solvent II is greater than 2, for example, can be selected from 2.05, 2.43, 2.76, 2.8, 3.23, 3.64, 3.65, 4.44, 5.2, 6, 10.09, 10.67, 10.89, 11.52, 11.61, 11.88, 12.32, 17.54, 17.71, 18 .32, 18.34, 18.46, 18.68, 19.12, 21.92, 22.01, 22.72, 31.22, 31.23, 31.31, 31.36, 31.39, 31.58, 31.8, 32.02, 35.12, 35.13, 35.21, 35.26, 35.29, 35.48, 35.7, 35.92.

[0025] In some preferred embodiments of the present invention, the difference between the relative dielectric constants of the solvent I and the solvent II is greater than 11.

[0026] When the difference between the relative dielectric constants of solvent I and solvent II is less than 2, the mutual solubility of solvent I and solvent II is enhanced, and it is difficult for solvent II to meet the conditions of the particle gap formed by solvent I and the mixed powder. Most of solvent II will form a mixed liquid with solvent I to wrap the powder, resulting in uneven distribution of pore positions and poor pore-forming effect, and it is impossible to obtain an anode layer with a specific porosity after sintering.

[0027] In some embodiments of the present invention, the ceramic powder is selected from at least one of zirconium oxide, aluminum oxide, magnesium oxide, titanium dioxide, and aluminum nitride.

[0028] In some embodiments of the present invention, the metal oxide is selected from at least one of nickel-containing metal oxides, iron-containing metal oxides, cobalt-containing metal oxides, nickel-iron metal oxides, and cobalt-iron metal oxides; in some embodiments of the present invention, the metal oxide is selected from at least one of NiO, Fe3O4, Co2O3, nickel ferrite NiFe2O4, and cobalt ferrite CoFe2O4.

[0029] In some embodiments of the present invention, the binder is selected from at least one of acrylic polymers, polymethyl methacrylate, and polyvinyl butyral.

[0030] In some embodiments of the present invention, the acrylic polymer comprises a methacrylic polymer.

[0031] In some embodiments of the present invention, the dispersant is selected from at least one of castor oil, alkyl aryl sulfonate, and polyethylene glycol.

[0032] In some embodiments of the present invention, the plasticizer is selected from at least one of dimethyl phthalate, dibutyl phthalate, and dioctyl phthalate.

[0033] In some embodiments of the present invention, the porosity of the anode layer is 48-58%, and the strength of the anode layer is 210-380 MPa.

[0034] In some embodiments of the present invention, the porosity of the anode layer can be selected from 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%. In some embodiments of the present invention, the strength of the anode layer is 210MPa, 220MPa, 230MPa, 240MPa, 250MPa, 260MPa, 270MPa, 280MPa, 290MPa, 300MPa, 310MPa, 320MPa, 330MPa, 340MPa, 350MPa, 360MPa, 370MPa, 380MPa.

[0035] The second aspect of the present invention provides an anode-supported solid oxide battery, comprising the anode layer described in the first aspect of the present invention.

[0036] The third aspect of the present invention provides a method for preparing the anode-supported solid oxide battery according to the second aspect of the present invention, comprising the following steps:

[0037] S1: mixing and grinding the raw materials for preparing the anode layer to obtain an anode layer slurry;

[0038] S2: tape-casting the anode layer slurry to obtain an anode layer green body:

[0039] S3: printing an electrolyte layer on the anode layer green body to obtain a half-cell green body;

[0040] S4: debinding and sintering the half-cell green body to obtain a sintered body;

[0041] S5: preparing a cathode on the sintered body, and then sintering to obtain the anode-supported solid oxide battery.

[0042] In some embodiments of the present invention, the step S1 is: after mixing the ceramic powder and the metal oxide, mix them with solvent I, dispersant and plasticizer, and then mix them with solvent II and binder to obtain anode layer slurry. In some embodiments of the present invention, the step S1 is: after mixing the ceramic powder and the metal oxide, mix them with solvent I, dispersant and plasticizer for 4 to 8 hours, and then mix them with solvent II and binder for 10 to 20 hours, so that the viscosity of the slurry reaches 2 to 4 Pa·s, and obtains anode layer slurry. In the preparation method of the present invention, the ceramic powder and the metal oxide are first mixed, so that the composition of the mixed powder is more uniform, and then mixed with solvent I, dispersant and plasticizer, so that solvent I completely wraps the mixed powder to form "core-shell" particles, and then mixed with solvent II and binder, so that solvent II can be fully dispersed between the "core-shell" particles, so that the pore size distribution in the obtained anode layer is more uniform.

[0043] In some embodiments of the present invention, the thickness of the solid electrolyte layer is 5 to 20 μm.

[0044] In some embodiments of the present invention, the debinding temperature in step S4 is 300-500°C, for example, can be selected from 300°C, 350°C, 400°C, 450°C, 500°C.

[0045] In some embodiments of the present invention, the debinding and heat preservation time in step S4 is 5 to 8 hours, for example, can be selected from 5 hours, 6 hours, 7 hours, and 8 hours.

[0046] In some embodiments of the present invention, the sintering temperature in step S4 is 1300-1500°C, for example, can be selected from 1300°C, 1320°C, 1340°C, 1360°C, 1380°C, 1400°C, 1420°C, 1440°C, 1460°C, 1480°C, 1500°C.

[0047] In some embodiments of the present invention, the sintering holding time in step S4 is 8 to 12 hours, for example, can be selected from 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.

[0048] In some embodiments of the present invention, the heating rate of step S4 is 50-70°C / h, for example, it can be selected from 50°C / h, 51°C / h, 52°C / h, 53°C / h, 54°C / h, 55°C / h, 56°C / h, 57°C / h, 58°C / h, 59°C / h, 60°C / h, 61°C / h, 62°C / h, 63°C / h, 64°C / h, 65°C / h, 66°C / h, 67°C / h, 68°C / h, 69°C / h, 70°C / h. In the present invention, the heating rate affects the volatilization rate of solvent I and solvent II. When the heating rate is 50-70°C / h, it is beneficial to obtain an anode layer with a more uniform pore size distribution.

[0049] In some embodiments of the present invention, the step S5 is: preparing a cathode on the sintered body by screen printing, and then sintering at 1000-1100° C. to obtain the anode-supported solid oxide battery.

[0050] In some embodiments of the present invention, the thickness of the cathode is 20-50 μm.

[0051] In some embodiments of the present invention, the cathode is a LSCF cathode.

[0052] The fourth aspect of the present invention provides use of the anode layer described in the first aspect of the present invention in the field of batteries.

[0053] The beneficial effect of the present invention is that the anode layer in the present invention adopts an organic solvent as a pore-forming agent, which can better control the pore size, pore size distribution and porosity in the anode layer compared with existing solid pore-forming agents, so that the prepared anode layer has a more uniform pore size distribution, higher porosity and higher supporting strength, thereby improving the power generation efficiency and service life of the solid oxide fuel cell.

[0054] Since the relative dielectric constant difference of solvent I and solvent II in the present invention is greater than 2, the two cannot be miscible. In the process of preparing the anode layer, solvent I wraps the mixed powder to form a "core-shell" structure, and solvent II is distributed between the "core-shell" structure formed by solvent I and the mixed powder. When solvent I and solvent II evaporate, a microscopic morphology with good pore size and distribution uniformity and high porosity will be formed in the anode layer. By controlling the mass relationship between solvent I, solvent II and the mixed powder, the anode layer has both high porosity and high support strength. In addition, solvent I and solvent II in the present invention have no residue in the anode layer and will not affect the various properties of the anode layer. DETAILED DESCRIPTION

[0055] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0056] The raw material information used in the examples and comparative examples of the present invention is as follows:

[0057] The binder is polymethyl methacrylate (PAA);

[0058] The dispersant is castor oil;

[0059] The plasticizer is dimethyl phthalate (DMP);

[0060] The mixed powder is a mixed powder of zirconium oxide and nickel oxide, wherein the mixed powders used in Examples 1 to 3, Examples 6 to 15 and Comparative Examples 1 to 7 are all mixed powders of zirconium oxide and nickel oxide in a mass ratio of 2:1, the mixed powder used in Example 4 is a mixed powder of zirconium oxide and nickel oxide in a mass ratio of 1:1, and the mixed powder used in Example 5 is a mixed powder of zirconium oxide and nickel oxide in a mass ratio of 3:1.

[0061] Example 1

[0062] This example provides an anode layer for a solid oxide battery, which is made of the following raw materials in the following mass percentages: 35% mixed powder, 40% organic solvent, 8% binder PAA, 2% dispersant castor oil, and 15% plasticizer dimethyl phthalate (DMP). The specific formula of the anode layer is shown in Table 1, wherein the mixed powder is a mixture of zirconium oxide and nickel oxide in a mass ratio of 2:1; taking the total mass percentage of the raw materials of the anode layer as 100%, the organic solvent is composed of 28.06% by mass of acetonitrile (solvent I) and 11.94% by mass of n-hexane (solvent II), the relative dielectric constant of acetonitrile is 37.5, the relative dielectric constant of n-hexane is 1.58, the relative dielectric constant difference between acetonitrile and n-hexane is 35.92, and the mass ratio of acetonitrile to n-hexane is 2.35:1; the mass ratio of n-hexane to the mixed powder is 0.34, and the formula and relative dielectric constant of the organic solvent in the raw materials for preparing the anode layer are shown in Table 2.

[0063] Embodiments 2 to 15

[0064] The formula of the anode layer for the solid oxide battery in Examples 2 to 15 is shown in Table 1 below, and the formula and relative dielectric constant of the organic solvent in the raw materials for preparing the anode layer are shown in Table 2 below.

[0065] Comparative Examples 1 to 7

[0066] The formula of the anode layer for solid oxide batteries in Comparative Examples 1 to 7 is shown in Table 1 below, and the formula and relative dielectric constant of the organic solvent in the raw materials for preparing the anode layer are shown in Table 2 below.

[0067] Table 1 Formulation of the anode layer in Examples 1 to 15 and Comparative Examples 1 to 7 (unit: mass percentage)

[0068] Mixed powder / % Organic solvent / % Binder / % Dispersant / % Plasticizer / % Example 1 35 40 8 2 15 Example 2 30 50 10 1 9 Example 3 50 25 5 3 17 Example 4 30 50 10 1 9 Example 5 50 25 5 3 17 Example 6 45 40 8 2 5 Example 7 45 40 8 2 5 Example 8 45 40 8 2 5 Example 9 45 40 8 2 5 Example 10 45 40 8 2 5 Embodiment 11 35 40 8 2 15 Example 12 35 40 8 2 15 Example 13 35 40 8 2 15 Embodiment 14 35 40 8 2 15 Embodiment 15 35 40 8 2 15 Comparative Example 1 55 20 5 3 17 Comparative Example 2 25 55 10 1 9 Comparative Example 3 35 40 8 2 15 Comparative Example 4 35 40 8 2 15 Comparative Example 5 35 40 8 2 15 Comparative Example 6 35 40 8 2 15 Comparative Example 7 35 40 8 2 15

[0069] Table 2 Formula and relative dielectric constant of organic solvents in raw materials for anode layer preparation

[0070]

[0071]

[0072] Note: In Table 2, the mass percentages of solvent I and solvent II are calculated based on the total mass percentage of the raw materials of the anode layer being 100%.

[0073] The raw materials for preparing the anode layers in Examples 1 to 15 and Comparative Examples 1 to 7 were prepared into a single cell structure (i.e., an anode-supported solid oxide cell) that can be used for testing according to the following preparation method. The specific preparation steps are as follows:

[0074] Step S1: Weigh the formula amount of zirconium oxide and nickel oxide and mix them to prepare a mixed powder, add the mixed powder, solvent I, dispersant and plasticizer in a ball mill in sequence and mix them thoroughly for 6 hours; then add solvent II and binder and continue mixing for 15 hours, control the viscosity of the mixed slurry measured at 25° C. to be in the range of 2 to 4 Pa·s, and obtain an anode layer slurry;

[0075] Step S2: The anode layer slurry obtained in step S1 is tape-cast to obtain an anode layer green body with a thickness of 480 μm;

[0076] Step S3: printing an electrolyte layer on the anode layer green body obtained in step S2, wherein the electrolyte layer has a thickness of 15 μm, to obtain a half-cell green body;

[0077] Step S4: placing the half-cell green body prepared in step S3 in a high-temperature furnace for debinding and sintering treatment, with a debinding temperature of 400°C, a heating rate of 60°C / h, a holding time of 6h, a sintering temperature of 1400°C, a holding time of 10h, and a sintered body after sintering.

[0078] Step S5: The sintered body prepared in step S4 is screen-printed with an LSCF cathode and sintered. The cathode thickness is 30 μm, the sintering temperature is 1100° C., and the sintering time is 4 h. After sintering, a single cell structure that can be used for testing is obtained.

[0079] Then, the porosity, support strength and battery performance (ie, maximum power density) of the single cell structures prepared by Examples 1 to 15 and Comparative Examples 1 to 7 were tested respectively according to the performance testing method described in Table 3 below. The specific test results are shown in Table 4 below.

[0080] Table 3 Performance test method of the single cells prepared by Examples 1 to 15 and Comparative Examples 1 to 7

[0081]

[0082]

[0083] Table 4 Performance test results of the single cells prepared by Examples 1 to 15 and Comparative Examples 1 to 7

[0084] Porosity / % Support strength / MPa <![CDATA[Power density / (W / cm 2 )]]> Example 1 48.6 381 1.36 Example 2 52.9 290 1.12 Example 3 53.7 283 1.07 Example 4 52.6 302 1.18 Example 5 53.6 282 1.14 Example 6 57.8 213 1.34 Example 7 54.5 265 1.19 Example 8 54 270 1.2 Example 9 53.6 288 1.22 Example 10 53.2 294 1.23 Embodiment 11 48.6 376 1.28 Example 12 48.5 379 1.28 Example 13 48.5 378 1.27 Embodiment 14 48.4 380 1.26 Embodiment 15 48.4 380 1.23 Comparative Example 1 20.7 505 0.86 Comparative Example 2 58.7 190 0.98 Comparative Example 3 60.1 183 1.03 Comparative Example 4 47.9 397 1.02 Comparative Example 5 9.7 625 0.75 Comparative Example 6 15.3 543 0.99 Comparative Example 7 15.8 537 1.01

[0085] It can be seen from Table 4 that the anode layers in Examples 1 to 15 of the present invention all have a relatively high porosity (not less than 48%), a relatively strong supporting strength (not less than 210 MPa) and a relatively large power density (≥1.0 W / cm 2). In Comparative Example 1, the amount of mixed powder used is too much and the amount of organic solvent used is too little, so the porosity and power density of the obtained anode layer are not up to standard. In Comparative Example 2, the amount of mixed powder used is too little and the amount of organic solvent used is too much, so the porosity of the obtained anode layer is too high, resulting in insufficient support strength of the anode layer and substandard power density. In Comparative Example 3, the ratio of solvent I to solvent II is lower than 0.7, that is, the amount of solvent II used is relatively excessive, and the porosity of the obtained anode layer is too large and the support strength is not up to standard. In Comparative Example 4, the ratio of solvent I to solvent II is higher than 2.7, that is, the amount of solvent II used is relatively too little, and the porosity of the obtained anode layer is lower than 48%. Comparative Example 5 uses only a single component acetonitrile as an organic solvent, and the porosity and power density of the obtained anode layer are not up to standard. The differences in relative dielectric constants of solvent I and solvent II used in Comparative Examples 6 and 7 are both less than 2, the porosity of the obtained anode layers does not meet the standards, and the power density of the anode layer in Comparative Example 6 does not meet the standards either.

[0086] In summary, the present invention adjusts the formula of the anode layer and uses solvent pore formation to achieve good control of the pore size and distribution of the anode layer, and prepares a pore with a porosity of 48-58%, a support strength of 210-380 MPa, and a power density of not less than 1.0 W / cm 2 The present invention provides an anode layer with excellent performance, and the anode layer can be used to prepare a high-performance anode-supported solid oxide battery.

[0087] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. An anode layer, characterized in that: The preparation comprises the following raw materials in percentage by mass: 30-50% of mixed powder, 25-50% of organic solvent, 5-10% of binder, 1-3% of dispersant, and 1-20% of plasticizer; The mixed powder includes ceramic powder and metal oxide; The organic solvent includes solvent I and solvent II, the difference between the relative dielectric constants of solvent I and solvent II is greater than 2; the mass ratio of solvent I to solvent II is (0.7-2.7):1; the mass ratio of solvent II to the mixed powder is (0.2-0.5):

1.

2. The anode layer according to claim 1, characterized in that: In the mixed powder, the mass ratio of the ceramic powder to the metal oxide is (1-3):

1.

3. The anode layer according to claim 1, characterized in that: The solvent I is selected from at least one of acetonitrile, methanol, ethanol, acetone, isopropanol, n-pentanol, tert-butanol, tetrahydrofuran, ethyl acetate, chloroform and ether; And / or, the solvent II is selected from at least one of m-xylene, toluene, benzene, carbon tetrachloride, dioxane, cyclohexane, petroleum ether and n-hexane.

4. The anode layer according to claim 1, characterized in that: The difference between the relative dielectric constants of the solvent I and the solvent II is greater than 11.

5. The anode layer according to claim 1, characterized in that: The ceramic powder is selected from at least one of zirconium oxide, aluminum oxide, magnesium oxide, titanium dioxide and aluminum nitride; And / or, the metal oxide is selected from at least one of nickel-containing metal oxides, iron-containing metal oxides, cobalt-containing metal oxides, nickel-iron-containing metal oxides, and cobalt-iron-containing metal oxides; And / or, the binder is selected from at least one of acrylic polymer, polymethyl methacrylate, and polyvinyl butyral; And / or, the dispersant is selected from at least one of castor oil, alkyl aryl sulfonate, and polyethylene glycol; And / or, the plasticizer is selected from at least one of dimethyl phthalate, dibutyl phthalate and dioctyl phthalate.

6. The anode layer according to any one of claims 1 to 5, characterized in that: The porosity of the anode layer is 48-58%, and the strength of the anode layer is 210-380 MPa.

7. An anode-supported solid oxide battery, characterized in that: The anode layer comprises the anode layer according to any one of claims 1 to 6.

8. The method for preparing the anode-supported solid oxide battery according to claim 7, characterized in that: The following steps are involved: S1: mixing and grinding the raw materials for preparing the anode layer according to any one of claims 1 to 6 to obtain an anode layer slurry; S2: tape-casting the anode layer slurry to obtain an anode layer green body: S3: printing an electrolyte layer on the anode layer green body to obtain a half-cell green body; S4: debinding and sintering the half-cell green body to obtain a sintered body; S5: preparing a cathode on the sintered body, and then sintering to obtain the anode-supported solid oxide battery.

9. The method for preparing an anode-supported solid oxide battery according to claim 8, characterized in that: The steps The debinding temperature in S4 is 300-500°C; And / or, the debinding and heat preservation time in step S4 is 5 to 8 hours; And / or, the sintering temperature in step S4 is 1300-1500° C.; And / or, the sintering holding time in step S4 is 8 to 12 hours.

10. Use of the anode layer according to any one of claims 1 to 6 in the field of batteries.